Rancang Bangun Sistem Air Mancur Otomatis Berbasis Mikrokontroler AT89S52 - ., Robert (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2013)
Today, the development of technology continues to increase, it can be seen from the increasing number of electronic devices that are used day to day, one of that is the maintenance of park. One important thing in making the city park is a fountain. The existence of a fountain can make the park atmosphere more attractive and beautiful. Most of the existing fountain spouting only static bursts (no variation), of course this will lead to boredom for park visitors if seen in a long time. The purpose of this research is how to design a fountain that can be controlled high and low water bursts, pattern of bursts and fountain lighting design so it looks more beautiful and attractive. This automatic fountain used microcontroller AT89S52 as master controller of systems. As for the plan to be controlled is the water pump, electric valves and electric lighting fountains. Microcontroller AT89S52 used assembler language which design using personal computer. Based on this research that has been completed, the automatic fountain show variations patterns of bursts and lighting  during 11 minutes 58 seconds for 1 cycle program. Keywords : Automatic Fountain, Assembler, Nozzle, Electric valve, Microcontroller AT89S52.